Konsumsi Sayur dan Buah pada Siswa Sekolah Dasar (Studi pada Makan Siang Sekolah dan Bekal) - Diani Zafira; Farapti Farapti (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2020)
ABSTRACTBackground: The consumption for vegetable and fruit in Indonesia was lower than recommendation World Health Organization 400g/day. School lunch and packed lunch could increased consumption of vegetable and fruit.Objective: To analyze differences vegetable and fruit consumption between school lunch and packed lunch group.Method: This was a cross-sectional study involving 155 students with 47 sampels for school lunch and 108 sampels for packed lunch group in SD Muhammadiyah 4 Surabaya. Respondents were interviewed with questioner using food recall method for 2x24 hours, observed intake of vegetables and fruit during lunch and intake a day compared between school lunch and packed lunches. Data were analyzed using independent t-test.Result: Average consumption of vegetables and fruit between two groups was significant, vegetables (p<0.001) and fruit (p<0.001). The amount of vegetable and fruit consumption in the school lunch group averages 26.66 g and 25.53 g and packed lunch groups only 5.09 g and 3.24 g. There was no difference in two groups for consumption of vegetables (p = 0.322) and fruit (p = 0.473). Amount of consumption of vegetables and fruits a day in school lunch group was 28.88 g and 31.81 g, while in packed lunch group only 18.08 g and 25.46 g.Conclusions: There were differences of the consumption of vegetables and fruits between two groups. School lunch and packed lunch standard to increase intake and reduce vegetables and fruits waste in school lunch is needed.ABSTRAKLatar belakang: Konsumsi sayur dan buah di Indonesia tergolong rendah dibanding anjuran World Health Organization 400g/hari. Upaya meningkatkan asupan sayur dan buah anak usia sekolah ialah melalui program makan siang sekolah dan bekal.Tujuan: Menganalisis perbedaan konsumsi sayur dan buah antara kelompok makan siang sekolah dan bekal.Metode: Penelitian Cross-sectional ini melibatkan 155 siswa yang dibagi menjadi 47 siswa kelompok makan siang sekolah dan 108 siswa kelompok bekal. Penelitian dilakukan di SD Muhammadiyah 4 Surabaya. Kuesioner yang digunakan adalah food recall selama 2x24 jam, observasi asupan sayur dan buah ketika makan siang dan asupan sehari dibandingkan antara makan siang sekolah dan bekal. Analisis menggunakan uji independen t-test.Hasil: Rata-rata konsumsi sayur dan buah saat makan siang pada kelompok makan siang sekolah dan kelompok bekal menunjukkan perbedaan signifikan yakni sayur (p<0,001) dan buah (p<0,001). Jumlah konsumsi sayur dan buah pada kelompok makan siang sekolah rata-rata 26,66 g dan 25,53 g dan kelompok bekal hanya 5,09 g dan 3,24 g. Rata-rata konsumsi sayur dan buah sehari tidak ada perbedaan pada 2 kelompok baik sayur (p=0,322) dan buah (p=0,473). Jumlah konsumsi sayur dan buah sehari kelompok makan siang sekolah ialah 28,88 g dan 31,81 g, sedangkan pada kelompok bekal hanya 18,08 g dan 25,46 g.Kesimpulan: Terdapat perbedaan konsumsi sayur dan buah antara kelompok makan siang sekolah dengan bekal. Perlu adanya standar makan siang sekolah dan makanan bekal untuk meningkatkan asupan dan mengurangi sisa sayur dan buah pada makanan siang sekolah.